2019
DOI: 10.1177/1533033819876981
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Hypofractionated Stereotactic Radiotherapy Using CyberKnife for High Volume Cavernous Sinus Cavernous Hemangiomas

Abstract: Objective: To evaluate the efficacy and safety of hypofractionated stereotactic radiotherapy using CyberKnife for high volume cavernous sinus cavernous hemangiomas. Materials and Methods: We collected data from 12 patients with high volume cavernous sinus cavernous hemangiomas treated with hypofractionated stereotactic radiotherapy using CyberKnife in our institute, including 2 men and 10 women/female child, aged 4 to 60 years. Initial tumor volumes ranged from 11.8 to 96.6 cm3 with a median of 24.3 cm3. Irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…CyberKnife treatment [18][19][20] and radiotherapy 22,23 have both been reported to result in impressive tumor control and low side-effect incidence in treating large or giant CSHs, findings which also indicate the sensitivity of CSHs to radiation treatment. In comparison, the radiation dose of GKRS is distributed in layers, like an onion, which makes the radiation dose to the tumor center 2 times higher than the dose to the tumor margin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…CyberKnife treatment [18][19][20] and radiotherapy 22,23 have both been reported to result in impressive tumor control and low side-effect incidence in treating large or giant CSHs, findings which also indicate the sensitivity of CSHs to radiation treatment. In comparison, the radiation dose of GKRS is distributed in layers, like an onion, which makes the radiation dose to the tumor center 2 times higher than the dose to the tumor margin.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to GKRS, the reported therapies for giant CSHs include microsurgical resection, [2][3][4][5]28 CyberKnife therapy, [18][19][20] and radiotherapy. 22,23 Li et al 2 retrospectively reviewed surgical results of 47 patients with large-volume CSHs and gross-total resection in 26 (55.3%) cases with average intraoperative blood loss of 650 ml (range 100-3500 ml), and found that increased tumor size was a risk factor for unfavorable outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CyberKnife (CK) is a relatively less-invasive modality among radiosurgical treatments. Hypofractionated stereotactic radiotherapy (HSRT) with CK can reduce radiation toxicity on the surrounding structures with short treatment duration and thus holds a distinguished efficacy for metastatic brain tumors, 1 , 2 ) meningiomas, 3 ) cavernous malformations, 4 ) and small arteriovenous malformations (AVMs). 5 , 6 ) However, it is believed that no reports exist regarding HSRT with CK for AVMs that are difficult to treat (e.g., large AVMs and AVMs located in eloquent areas).…”
Section: Introductionmentioning
confidence: 99%